Familial Predisposition to Leiomyomata: Searching for Protective Genetic Factors - Maria V. Kuznetsova; Nelly S. Sogoyan; Andrew J. Donnikov; Dmitry Y. Trofimov; Leila V. Adamyan; Natalia D. Mishina; Jekaterina Shubina; Dmitry V. Zelensky; Gennady T. Sukhikh (Biomedicines, 2022)
In order to determine genetic loci associated with decreasing risk of uterine leiomyomata (UL), a genome-wide association study (GWAS) was performed. We analyzed a group of patients with a family history of UL and a control group consisting of patients without uterine fibroids and a family predisposition to this pathology. Six significant single nucleotide polymorphisms were selected for PCR-genotyping of a large data set of patients with UL. All investigated loci (rs3020434, rs11742635, rs124577644, rs12637801, rs2861221, and rs17677069) demonstrated the lower frequency of minor alleles within a group of women with UL, especially in a subgroup consisting of patients with UL and a familial history of leiomyomata. We also found that the minor allele frequencies of these SNPs in our control group were higher than those across the Caucasian population in all. Based on the obtained data, an evaluation of the common risk of UL was performed. Further work will pave the way to create a specific SNP-panel and allow us to estimate a genotype-based leiomyoma incidence risk. Subsequent studies of genetic variability in a group of patients with a familial predisposition to UL will allow us to make the prediction of the development and course of the disease more individualized, as well as to give our patients personalized recommendations about individual reproductive strategies.